Table of Content - -, (Journal of Arabic Language Sciences and Literature, 2024)
Table of Content:1. Unrecorded Lexis in the Annotation of the Hudhaliyyin Poems by Al-Sukkari (275 AH),  from the beginning of the book to the end of Al-Mu’atal Al-Hudhali’s PoetryMr. Shehu Yakubu Adedeji2. The Dualism Generosity and miserliness in the dewan Ibn Himyar Al-Hamdani. cultural readingMr. Musaddif Mousa Alnami3. The Value of Pre-Islamic Poetry in Ibn Abd Rabbuh’s “Aleqd” and his PoetryDr. Jamal Ali Ghidan4. Effect of mobile learning on learning reading skills among female learners of Arabic Language  as a second languageMs. Lulua Abdullh Saeed Al-Shahrani5. Departure to ruins in pre-Islamic poetry: A study in the semiotics of emotional and existential outcomeMs. Amal Qasem Mohammed Melhi Al-Zomor, Dr. Mohd Ala Uddin Bin Othman, Prof.  Elsayed Mohammed Salem6. The Verb "Ja'ala" in the Holy Quran: A Semiotic Study of Selected Examples from the Verses of the Holy QuranMr. Sami Hamed Al-Maliki
Keywords: Journal of Arabic Language and Literature